Laetosphecia, a new genus of clearwing moths from south-eastern China, with a brief review of the Sesiini from China (Lepidoptera, Sesiidae) - Kallies, Axel; Arita, Yutaka; Owada, Mamoru; Wang, Min (Zootaxa, 2014)
In this study, a new genus of Sesiini, Laetosphecia Kallies & Arita gen. nov., is described. The type species, Laetosphecia variegata (Walker, 1865) comb. nov., and a new species, Laetosphecia brideliana Kallies & Arita spec. nov., occur in south-eastern China (Province of Guangdong and Hong Kong). The larvae of both species cause galls in small branches of Bridelia tomentosa Blume (Phyllanthaceae). Furthermore, Laetosphecia leucozona (Hampson, 1919) comb. nov. from north-eastern India is transferred to the new genus. Additionally, we briefly review the Sesiini fauna of Mainland China and present an updated checklist for this region. Trilochana caseariae Yang & Wang, 1989 syn. nov. is established as a junior synonym of Trilochana scolioides Moore, 1879. Lenyra ashtaroth (Westwood, 1848) and Sphecosesia rhodites Kallies & Arita, 2004 are reported from China for the first time.